Towards network assessment of permanent railway track deformation. (July 2021) - Zuada Coelho, Bruno; Varandas, José Nuno; Hijma, Marc P.; Zoeteman, Arjen
Abstract: The permanent railway track deformation caused by regular train traffic is important for infrastructure managers and railway contractors, as it determines the railway track quality. Although several successful approaches have been made to address the topic of the permanent railway track deformation, these have only been applied at specific locations, and have not yet been successfully applied at a network level. This paper presents a methodology that can be applied at the network level, by making use of a stochastic subsoil model to characterise the subsoil uncertainty and variability along the railway line, and by combining it with a dynamic train-track model and a cumulative cyclic deformation model. This methodology is illustrated by analysing a railway track section of 9 km in the Netherlands. The effects of the train service, such as train speed and axle loads, on the permanent deformation of the track are quantified. The proposed methodology has been partially validated against results of the dynamic stiffness obtained during the passage of a measurement train. The results illustrate the added value of this methodology for infrastructure managers and railway contractors as it allows for the quantification, at network level, of the consequences of train service changes for the future state of the railway network.